2012
DOI: 10.1063/1.4737888
|View full text |Cite
|
Sign up to set email alerts
|

A simply constructed but efficacious shock tester for high-g level shock simulation

Abstract: A simply constructed shock tester, different from existing drop table machines, is developed for high-g level shock environment simulation. The theoretical model, structure design, and working principle of the drop tester are described. A prototype device is set up, where a carbon fiber reinforced polymer with a high specific modulus is used. Using a Brüel & Kjær high-g accelerometer, experiments to verify the validity of the design are carried out and results are given. The maximum acceleration level is in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Driven by the technical demands of high-g shock tests and inspired by existing ideas, a compact high-g shock tester with a three-body vertically stacked shock amplifier was developed by the current authors. The experimental results confirmed that this design was successful [25][26][27] . However, a detailed study of the velocity amplification seems to have been deliberately ignored, most likely because the primary focus was on the shock acceleration pulse parameters.…”
supporting
confidence: 69%
“…Driven by the technical demands of high-g shock tests and inspired by existing ideas, a compact high-g shock tester with a three-body vertically stacked shock amplifier was developed by the current authors. The experimental results confirmed that this design was successful [25][26][27] . However, a detailed study of the velocity amplification seems to have been deliberately ignored, most likely because the primary focus was on the shock acceleration pulse parameters.…”
supporting
confidence: 69%
“…The impact table is suspended by a spring and can slide along the hole within the upper-stand cover. The upper-stand cover and the upperstand are threaded together to guarantee that the impact table and the object mounted on it have the same initial velocity as the drop rod assembly [16]. The sliding ring, fixed to the carbon fiber reinforced polymer rod (CFRPR) to support the reaction force of the driving spring, slides along the inner wall of the hole in the shell.…”
Section: Description and Operationmentioning
confidence: 99%
“…Our design inspiration for the shock tester comes from the concepts of shock velocity amplification developed by Rodgers et al and down-hole hammer rebound also investigated by Rodgers et al [11][12][13][14][15]. The detailed designs and test results of a prototype device can be found in [16]. Here the properties (including acceleration range, pulse 0957-0233/13/045901+06$33.00 durations and reproducibility) of the complete shock tester are experimentally investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Such parts or systems working in the harsh inertial environments must strictly test for design qualification, survivability testing, and calibration. For specimens with variable weights and sizes, now available experimental technologies include pendulum striker, drop machines, Hopkinson pressure bar, free fall drop test devices, air gun, rail gun, explosion near field simulation, and warhead penetration [2][3][4][5][6][7][8][9][10][11][12]. e inspiration of this paper comes from the fact that a compressed air cannon can produce instantaneous and powerful air jets that can be used to drive the tested object to achieve a high initial collision velocity.…”
Section: Introductionmentioning
confidence: 99%